Supplementation of Dietary Crude Lentinan Improves the Intestinal Microbiota and Immune Barrier in Rainbow Trout (Oncorhynchus mykiss) Infected by Infectious Hematopoietic Necrosis Virus - Ren, Guangming; Xu, Liming; Zhao, Jingzhuang; Shao, Yizhi; Chen, Xiaoyu; Lu, Tongyan; Zhang, Qiya (Frontiers in Immunology, 2022)
Effect of crude lentinan (CLNT) on the intestinal microbiota and immune barrier were evaluated in rainbow trout (Oncorhynchus mykiss) infected by infectious hematopoietic necrosis virus. The results showed that supplementary CLNT declined the rainbow trout mortality caused by IHNV, which suggested CLNT has preventive effects on IHNV infection. IHNV destroyed intestinal integrity, as well as caused the intestinal oxidative and inflammatory damages in rainbow trout. Supplementary CLNT strengthened intestinal immune barrier through declining the intestinal permeability, as well as enhancing intestinal antioxidant and anti-inflammatory ability in IHNV infected rainbow trout. In addition, CLNT modified the aberrant changes of intestinal microbiota induced by IHNV, mainly representing by promoting the growth of Carnobacterium and Deefgea, and inhibiting Mycobacterium and Nannocystis. Especially, supplement with CLNT promoted the growth of SCFAs producing bacteria and consequently increased the production of acetic acid, butanoic acid and hexanoic acid in intestine of IHNV infected rainbow trout. Furthermore, it was speculated that CLNT could regulate the self-serving metabolic pathways of intestinal microbiota induced by IHNV, such as fatty acid metabolism and amino acid metabolism. Together, CLNT played the antiviral effects on IHNV infection through strengthening intestinal immune barrier, as well as regulating intestinal microbiota and SCFAs metabolism in rainbow trout. The present data revealed that CLNT exerted a promising prebiotic roles in preventing the rainbow trout from IHNV infection.